Topological Descriptors and Polynomials of Hourglass Benzenoid Series HBk: k ? 1 - Alameri, Abdu; Zeren, Yusuf; Alsharafi, Mohammed (Yildiz Technical University, 2024)
Topological indices and coindices, numerical quantities derived from the chemical graph of a molecule, are widely employed in modeling the physicochemical properties of molecular compounds. This research focuses on the investigation of various topological descriptors of the Hourglass Benzenoid series ?=HB_k. Specifically, we compute and analyze a range of topological descriptors for the HB_k series, including well-established indices such as the generalized modified Zagreb indices. Additionally, we derive the polynomial indices of the molecular graphs associated with the HB_k series.